A randomized clinical trial of a simplified technique for complete denture fabrication: patient perceptions, masticatory efficiency, temporomandibular disorders and quality of dentures - Pascoal, Ana Luísa Barros; Paulino, Marcília Ribeiro; Oliveira, Angelo Giuseppe Rocalli da Costa; Carreiro, Adriana da Fonte Porto; Mestriner Júnior, Wilson; Calderon, Patricia dos Santos (Brazilian Dental Science, 2024)
Objective: To evaluate the efficacy of a simplified technique for complete dentures (CD) fabrication focusing on patient-reported outcome measures (PROMs), masticatory efficiency (ME), temporomandibular disorders (TMD), and CD technical quality. Material and Methods: Fifty edentulous individuals were allocated into two groups based on the complete denture (CD) fabrication method: traditional (T) or simplified (S). Patients were evaluated at baseline and at a 3-month follow-up, considering quality of life and satisfaction. The technical quality of the CDs and masticatory efficiency were assessed at the 3-month follow-up using a validated instrument and a colorimetric test, respectively. Data were analyzed using McNemar and Mann-Whitney tests for intra-group comparisons and Chi-square, Fisher’s Exact, or Wilcoxon tests for inter-group comparisons. Results: Forty-two patients completed the study (T = 20, S = 22). At the 3-month follow-up, no significant differences were observed between the groups for masticatory efficiency (p = 0.131), CD technical quality (p = 0.456), satisfaction (p = 0.146), and quality of life (p = 0.409). Patient-reported outcome measures (PROMs) improved from baseline to the 3-month follow-up (p < 0.01) for both groups. The presence of temporomandibular disorders (TMD) significantly decreased after denture replacement (p < 0.001). Conclusion: CD fabricated by a simplified technique seems to be time-efficient and as effective as that fabricated by a traditional technique. Insertion of new dentures positively influenced PROMs and TMD presence. KEYWORDS Complete denture; Mastication; Patient satisfaction; Quality of life; Temporomandibular disorders.